Citogenética clássica e molecular em peixes neotropicais. Estudos comparativos entre bacias hidrográficas com ênfase em região de transposição de rio - Silva, Elisangela Bellafronte da (Universidade Federal de São Carlos, 2009)
Basic and molecular cytogenetic studies were carried out in a few fish species from family Parodontidae: Apareiodon ibitiensis, A. piracicabae, A. affinis, A. vladii, Apareiodon sp. Parodon nasus and Parodon hilarii. All were collected in distinct hydrographic basins, with emphasis in a river transposition area, more specifically of the Piumhi River. Apareiodon. ibitiensis from the Upper Paraná River and Apareiodon sp. A from the São Francisco River presented the same chromosomal characteristics, as also observed in A. piracicabae in relation to Apareiodon sp. B. The presence of simple sex chromosomes of the ZZ/ZW type was verified in A. ibitiensis and Apareiodon sp., where the presence of the heterochromatin that originated the W chromosome was identified through C-band staining with propidium iodide. Fluorescent in situ hybridizations (FISH) with 18S and 5S ribosomal DNAs were performed in A. affinis, A. piracicabae and A. ibitiensis, resulting in a single chromosome pair marked with 5S rDNA in the three species, all in distinct chromosome pairs. The 18S rDNA is also present in one pair in A. affinis and A. piracicabae, but was polymeric among A. ibitiensis populations. While the 18S rDNA is more conserved in the Parodontidae species, the 5S rDNA may be considered a cytotaxonomical character for the group. FISH with pPh2004 satellite DNA isolated from P. hilarii was also performed in A. piracicabae, A. ibitiensis, A. vladii, A. affinis, Apareiodon sp. and P. nasus, but markings were only found in P. nasus. and A. affinis. When compared to other species where FISH with pPh2004 was carried out, two groups form: 1) the presence of this DNA in all the Parodon species, and 2) the absence in almost of the analyzed Apareiodon species, suggesting the maintenance of these genera. After the chromosomal characterization and confirmation of the species Apareiodon ibitiensis and Apareiodon piracicabae, besides Parodon nasus in distinct localities of the São Francisco River basin (regions of the Três Marias and the Piumhi River transposition), a cytogenetic tracking of the Parodontidae species in this hydrographic basin was made possible, which can be justified through natural (Piumhi Pantanal) and anthropogenic (Piumhi River transposition) connections between the Upper Paraná and the São Francisco River basins. Besides the Parodontidae species, Gymnotiformes species (Eigenamnnia virescens and Gymnotus sylvius) also described for the Upper Paraná basin are distributed in the São Francisco basin, and the transfer probably occurred through the Pantanal or the transposition. Cytogenetic analyses with a larger number of tools in the family Parodontidae was important for a better understanding of the evolution of this fish group, besides having been an important tool in the comparison of allopatric Parodontidae, Gymnotidae and Sternopigydae species present in the Upper Paraná and São Francisco River basins.
Keywords: Citogenética; Transposição de águas - Piumhi, Rio; Espécies invasoras; CIENCIAS BIOLOGICAS::GENETICA